Legal Protection of Productive Credit Debtors Against the Execution of Fiduciary Collateral Objects Due to Breach of Performance - Moch Agus Siswanto; Made Warka; Endang Prasetyawati; Krisnadi Nasution (Technium Social Sciences Journal, 2025)
The purpose of this dissertation is to understand and find the reconstruction of the regulation of legal protection for productive credit debtors against the execution of fiduciary collateral objects; to understand and find the execution of fiduciary collateral directly in the provisions of Article 30 of Law No. 42 of 1999 concerning justice-based fiduciary collateral. The legal issue in this dissertation is the existence of a legal vacuum where the regulation on credit, especially regarding productive credit debtors who use collateral objects for productive interests or debtors with consumptive credit, receive the same treatment for execution due to default based on the provisions of Article 30 of Law No. 42 of 1999 concerning Fiduciary Collateral. The recommendations from the results of this study are (1) There is a reconstruction of legal protection for productive credit debtors in Law No. 42 of 1999 concerning Fiduciary Collateral, especially regarding productive credit issues so that the productive sector that uses fiduciary collateral objects for productive activities can be maximized to improve community welfare. (2) Although the creditor party in the distribution of credit with fiduciary guarantee objects is a weak party and needs to be protected, this is accommodated in Law No. 42 of 1999 concerning Fiduciary Guarantee Objects.